E-commerce market trends: a case study in leveraging Web 2.0 technologies to gain and improve competitive advantage - Kiu, Ching Chieh; Lee, Chien Sing * (2017)
The emergence of Web 2.0 technologies has changed the way e-commerce can be sustained and improved to enhance competitive advantage. Integrating Web 2.0 technologies into e-commerce websites not only improves customer shopping experience but also enhances customer engagement. This paper examines Malaysian e-commerce engagement on Web 2.0 technology platforms to improve the customer shopping experience and customer engagement at their online retail store. The findings show that most of the Malaysia e-commerce websites have substantially integrated Web 2.0 technologies into their online retail store to gain and improve their competitive advantage. Furthermore, increased frequency of engagement in social mediums such as Facebook increases impact in terms of effect on customer shopping experience and customer engagement at online retail stores. In summary, Web 2.0 technologies influence changes in customer purchase behaviour, shopping experience and ultimately, the dramatic change in top ten ranking in the Malaysian e-commerce landscape.